Structure and Photoluminescence Characterization of LaPO4:Sm3+ Nanowires Prepared by Hydrothermal Method - Hien, Pham Thi Thanh; Huong, Duong Thi Mai; Long, Nguyen Ngoc; Vu, Le Van; Ha, Hoang Manh (VNU Journal of Science: Mathematics - Physics; Vol 31 No 4, 2015)
LaPO 4 nanowires doped with 1, 2,…8 mol% Sm 3+ were prepared by a hydrothermal method. The samples were characterized by transmission electron microscopy (TEM), X-ray diffraction (XRD), photoluminescence (PL), photoluminescence excitation (PLE), and absorption (ABS) spectroscopy. It was discovered that the PL and PLE of Sm 3+ ions resulted from the radiative intra-configurational f-f transitions. The photoluminescence spectra shows 4 peaks at 560 nm, 596 nm, 642 nm and 701 nm which were assigned to different transitions from the 4 G (4) 5/2 excited state to the 6 H J with J = 5/2; 7/2; 9/2; 11/2 ground states of Sm 3 + ion. The intensity of PL related to Sm 3+ ion reached to a maximum when the Sm doping content was 2 mol%. Diffuse reflective spectra measured at room temperature of the Sm 3+ doped LaPO 4 exhibited absorption peaks at 343, 362, 374, 401, 415, 439, 460 and 477 nm which were observed in PLE spectra as well. Keywords: Hydrothermal method, samarium doped lanthanum orthophosphate, nanowires